Modeling of armature melting and erosion process in high speed electrical sliding contact with rough surface - Xiaoquan Lu; Shaowei Liu; Xiangyu Du; Tianyou Zheng; Kefeng Yang (Scientific Reports)
Abstract Electromagnetic-thermal–mechanical coupling in high-speed current-carrying of armature and rail (A/R) sliding interface, which leads to armature melting and erosion, is a key challenge that restricts the performance of electromagnetic launch. In this study, a staged modeling method is adopted to construct a mathematical model of heat distribution and heat transfer during the armature pre-melting and post-melting phases. The study considers the multifactorial influences of contact resistance on the non-ideal rough surface, transient kinematic characteristics of the A/R, and loading pressure. The study also proposed a numerical computational method for fully implicit fast iterative tracking of the moving boundary of the molten layer, and systematically analyzed the melting process. The results show that the Joule heat at low speed is the key factor leading to the occurrence of armature melting, while the friction heat at high speed conditions has a significant effect on the armature maximum erosion depth when exiting the launcher. Measures such as the use of gallium-based liquid metal to prepare armature coatings or wear-resistant aluminum alloy materials can effectively alleviate the A/R interface damage problem. The research results provide a certain degree of revelation of the complex melting and erosion mechanism and the reliability design of the electromagnetic launching system.